SEGMENTASI CITRA BURUNG LOVEBIRD MENGGUNAKAN K-MEANS - Hero Diogenes Adoe; Aviv Yuniar Rahman; Istiadi Istiadi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Knowledge of the types of lovebirds is needed by lovebird lovers. The dominant color segmentation can provide information about the types of lovebirds. So the purpose of this research is to build a lovebird segmentation system using the K-means method. The research method used is image processing method. To carry out the segmentation process of the original image compared to the compressed image. Data collection is carried out by utilizing primary data in the form of pictures of lovebird birds which will later be processed using k means. Matlab is used to build a k means segmentation system. The data analysis stage in this study uses steps, data selection, preprocessing and data cleaning, data transformation, data mining, and evaluation/interpretation. The results of the study provide information that by using K-Means, the segmentation of lovebirds based on color can be detected. In this study, the lovebird image segmentation program using Matlab to extract RGB space to Greyscaled showed a higher accuracy rate of 96.26% than segmentation using manual methods, namely 85.19%.